2016
DOI: 10.22330/heb/311/060-073
|View full text |Cite
|
Sign up to set email alerts
|

Disgust and Facial Expression Recognition Across the Menstrual Cycle

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We supposed that if it is true that disgust can be 'projective' (Nussbaum, 2010;Rozin et al, 1986), then focusing on the dirty work environment that characterizes physically tainted occupations would promote disgust towards people who work in such an environment. In addition, our hypothesis was backedup by several authors (Buckels & Trapnell, 2013;Curtis & Biran, 2001;Haidt, McCauley & Rozin, 1994;Mikolić, 2016;Rozin et al, 2008), according to which bodily fluids and dirty environments can be considered culturally universal elicitors of disgust. Moreover, in order to demonstrate the importance of disgust in the severity of moral judgements, it is noteworthy that Schnall et al, (2008) used a dirty work setting to experimentally manipulate participants' disgust levels.…”
Section: Studymentioning
confidence: 77%
“…We supposed that if it is true that disgust can be 'projective' (Nussbaum, 2010;Rozin et al, 1986), then focusing on the dirty work environment that characterizes physically tainted occupations would promote disgust towards people who work in such an environment. In addition, our hypothesis was backedup by several authors (Buckels & Trapnell, 2013;Curtis & Biran, 2001;Haidt, McCauley & Rozin, 1994;Mikolić, 2016;Rozin et al, 2008), according to which bodily fluids and dirty environments can be considered culturally universal elicitors of disgust. Moreover, in order to demonstrate the importance of disgust in the severity of moral judgements, it is noteworthy that Schnall et al, (2008) used a dirty work setting to experimentally manipulate participants' disgust levels.…”
Section: Studymentioning
confidence: 77%
“…Prior research in this region has found that women perceive fetuses to be vulnerable to certain threats throughout the course of pregnancy , which opens the possibility that diseases, such as HIV, are viewed in a similar light. Alternatively, this finding could challenge the validity of maternal-fetal protection and related prophylactic theories since recent evidence suggests that maternal susceptibility to pathogens is not always limited to the first trimester (Kourtis et al 2014), and indicators of immunosuppression do not consistently predict hypothesized prophylactic behaviors both during pregnancy and across the menstrual cycle (Jones et al 2018;Mikolić 2016;Placek 2017;Placek and Hagen 2013;Timmers et al 2018).…”
Section: Maternal-fetal Protection Modelsmentioning
confidence: 99%